The edge of everything - Giles, Jeff (New York : Bloomsbury, 2017)
After rescuing seventeen-year-old Zoe and her little brother, a mysterious bounty hunter called X, sent from the Lowlands to claim the souls of evil men, risks everything for Zoe's love.
Keywords: Children's stories; Bounty hunters -- Fiction; Adventure and adventurers -- Fiction